In Vitro Production of Embryos from Abattoir-Derived Cattle Oocytes - Sianturi, Riasari Gail (2001)
Two studies involving some experiments were conducted to evaluate some factors affecting the in vitro production of cattle embryos from abattoir derived cattle oocytes. In the first study, more oocytes per ovary were recovered by slicing with a surgical blade (29.3 oocytes) than by aspiration with a disposable syringe and needle (12.0 oocytes). Cumulus expansion rate and maturation rate were better in oocytes surrounded by cumulus cells than in denuded oocytes and fibrinated oocytes. To determine the influence of adding serum and hormones, cumulus oocyte complexes (COCs) were matured in four different maturation media and incubated for 22 h at 39°C with 5% CO2 in humidified air. The addition of hormones to the maturation medium enhanced cumulus expansion rate and maturation rate. In the absence of hormones, 20% serum level rendered better cumulus expansion than with 10% serum but had no effect on the maturation rate. In the second study, factors affecting the IVF and the developmental competence of embryos were studied. In vitro matured oocytes were inseminated with swim-up separated sperm in IVF-TALP medium. At 18 or 44 h post insemination, the presumptive embryos were freed of cumulus and transferred into two culture media (lVC): modilled synthetic oviductal fluid (mSOF) as cell-free culture system and M199 with bovine oviductal epithelial cell (BOEC) as co-culture system. At 6 hour after inseminaton, male pronucleus formation was first observed. There were no signmcant differences on the effect of serum level (10% or 20%) and hormones supplementation in the maturation medium on the cleavage rate and developmental competence of embryos. Cleavage and blastocyst rates were 71.2% and 6.2% for cumulus-intact oocytes whereas the rates were 47.2% and 1.9% for cumulus-free oocytes. Although the cleavage rate was not different, better morula and blastocyst rates were obtained from co-culture system. The results indicate that hormones enhance cumulus cells expansion and maturation rates, cumulus cells facilitate fertilization while co-culture with BOEe rendered better developmental capacity of embryos. However, the failure of morula to develop to blastocysts in vitro needs further study.